(untitled) (Texas Journal of Medical Science, 2025)
Asthma is a chronic obstructive pulmonary disease that has persistent symptoms with intermittent periods of exacerbation, representing the reduction in health status. Chronic obstructive pulmonary disease has become fourth leading cause of death in 2021, responsible for approximately 5% of total deaths[1,2,3,4]]. Frequent, recurring periods of exacerbation may reach significant severity, and advanced therapy may become necessary, including the prescription of omalizumab, the anti-IgE monoclonal antibody. This meta-analysis aims to determine and systematically review the effect of omalizumab compared with the placebo in the control of severe asthma